Misi Bait Semesta sebagai Kerangka Teologi Alkitabiah untuk Menanggapi Sekularisme menurut Taksonomi Charles Taylor: A Biblical Theology Framework for Responding to Secularism According to Charles Taylor’s Taxonomy - Yohanes, Hendra (STT Reformed Injili Internasional, 2025)
The global Christian mission faces the pervasive context of secularism, presenting challenges and opportunities that require robust theological engagement. Charles M. Taylor categorizes secularism into three definitions: (1) separation between the sacred and the secular realm, but religion is axiomatic; (2) declining religious adherence in the purportedly neutral public sphere; and (3) a plurality of options is available for humans to construct the meaning of life. How does biblical theology respond to these three forms of secularism according to Taylor’s proposed taxonomy? This article proposes a “cosmic sanctuary mission” as a biblical theology framework for addressing the challenges in each of Taylor’s definitions of secularity. Employing the thematic-intertextual exegesis, it analyzes the biblical motifs of Eden and New Jerusalem, which bookend the biblical metanarrative. The intertextual links between Eden, New Jerusalem, and the temple highlight God’s dwelling place among His people. This biblical theology of cosmic sanctuary implies a theology of mission: to expand God’s holy place, beginning from Eden (Gen. 2) and consummating in New Jerusalem, which encompasses the whole cosmos (Rev. 21-22). This cosmic temple theology provides a holistic biblical framework for Christian mission, offering responses to each of Taylor’s definitions of secularism.